2020
DOI: 10.1152/japplphysiol.00604.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow responses to exercise are enhanced in left ventricular assist device patients after an exercise rehabilitation program

Abstract: Cerebral blood flow during exercise is impaired in patients with heart failure implanted with left ventricular assist devices (LVADs). Our aim was to determine whether a 3-mo exercise training program could mitigate cerebrovascular dysfunction. Internal carotid artery (ICA) blood flow and intracranial middle (MCA v) and posterior cerebral (PCA v) artery velocities were measured continuously using Doppler ultrasound, alongside cardiorespiratory measures at rest and in response to an incremental cycle ergometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Moreover, two studies reported a 43% and 53% increase of cerebral blood flow in patients with NYHA class III/IV heart failure following cardiac transplantation 21,22 . Similarly patients with heart failure treated with left ventricular assist devices experienced an increase of cerebral blood flow 23,24 . Finally, a large population‐based study in healthy older adults demonstrated that a lower cardiac index (cardiac output normalized for body surface area) was related to lower blood flow of the temporal lobes 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two studies reported a 43% and 53% increase of cerebral blood flow in patients with NYHA class III/IV heart failure following cardiac transplantation 21,22 . Similarly patients with heart failure treated with left ventricular assist devices experienced an increase of cerebral blood flow 23,24 . Finally, a large population‐based study in healthy older adults demonstrated that a lower cardiac index (cardiac output normalized for body surface area) was related to lower blood flow of the temporal lobes 25 .…”
Section: Discussionmentioning
confidence: 99%
“…20 In another study, 12 patients completed an unspecified HIIT protocol as part of a multimodal cardiac rehabilitation programme with improvement in cerebral blood flow during CPX. 30 Our findings open a pathway for the systematic application of this training modality in LVAD patients. Future studies should directly compare HIIT with MCT in patients with the lowest aerobic capacity and investigate its effects on peripheral and central determinants of oxygen consumption.…”
Section: Discussionmentioning
confidence: 62%
“…In one case report, a severely deconditioned patient, unable to tolerate MCT, improved after a short heart rate‐guided HIIT programme 20 . In another study, 12 patients completed an unspecified HIIT protocol as part of a multimodal cardiac rehabilitation programme with improvement in cerebral blood flow during CPX 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased ability of the brain to respond to physiological and regulatory stimuli is important for maintaining a healthy brain throughout life. Although several cross-sectional studies indicate an increase in general cerebrovascular function in people trained in exercise, a more recent study showed that dynamic cerebrovascular self-regulation is slightly attenuated in athletes after 6 weeks of high-intensity training (60). CO2 balneotherapy has long been applied clinically to improve cardiovascular symptoms in European countries.…”
Section: Discussionmentioning
confidence: 99%